Warming impacts on early life stages increase the vulnerability and delay the population recovery of a long‐lived habitat‐forming macroalga. (26th November 2018) - Capdevila, Pol; Hereu, Bernat; Salguero‐Gómez, Roberto; Rovira, Graciel·la; Medrano, Alba; Cebrian, Emma; Garrabou, Joaquim; Kersting, Diego K.; Linares, Cristina
Abstract: Understanding the combined effects of global and local stressors is crucial for conservation and management, yet challenging due to the different scales at which these stressors operate. Here, we examine the effects of one of the most pervasive threats to marine biodiversity, ocean warming, on the early life stages of the habitat‐forming macroalga Cystoseira zosteroides, its long‐term consequences for population resilience, and its combined effect with physical stressors. First, we performed a controlled laboratory experiment exploring the impacts of warming on early life stages. Settlement and survival of germlings were measured at 16°C (control), 20°C, and 24°C, and both processes were affected by increased temperatures. Then, we integrated this information into stochastic, density‐dependent integral projection models. Recovery time after a major disturbance significantly increased in warmer scenarios. The stochastic population growth rate ( λ s ) was not strongly affected by warming alone, as high adult survival compensated for thermal‐induced recruitment failure. Nevertheless, warming coupled with recurrent physical disturbances had a strong impact on λ s and population viability. Synthesis . The impact of warming effects on early stages may significantly decrease the natural ability of habitat‐forming algae to rebound after major disturbances. These findings highlight that, in a global warming context, populations of deep‐water macroalgae will become more vulnerable to further disturbances, and stress the need to incorporate abiotic interactions into demographic models. Abstract : The impact of warming effects on early stages may significantly decrease the natural ability of habitat‐forming algae to rebound after major disturbances. These findings highlight that, in a global warming context, populations of deep‐water macroalgae will become more vulnerable to further disturbances, and stress the need to incorporate abiotic interactions into demographic models.